ANALISIS EMISI KARBONDIOKSIDA DITINJAU DARI PENGGUNAAN KENDARAAN BERBASIS APLIKASI DI KECA-MATAN SUKOLILO SURABAYA (STUDI KASUS MASA PAN-DEMI COVID – 19) - Yayok Suryo Purnomo; Zarin Raffinet (EnviroUS, 2022)
Motor vehicles that are often used can have a serious impact, especially on the en-vironment. This study aims to determine CO2 emissions and the percentage of in-terest of vehicle users who want to switch to online-based vehicles so that there can be known to reduce the burden of CO2 emissions. The research method used the Mobile 6 equation and interviews with 59 vehicle users. The total result of CO2 emissions in Sukolilo Subdistrict amounted to 9,087,284.469 kg / year. The change in CO2 emissions from private vehicles to online motorcycles and online cars was 17.01% (1,528,256.816 tons of CO2/year) and 14.9% (1,341,380.027 tons of CO2/year). The selection of mo-tor bikes online has one of the most influential fac-tors, namely traffic congestion. As for the selection of online cars influenced by 2 significant factors, namely the factor of limited parking space and more comforta-ble for travel.